Variable factors in literary critical evaluation (on the examples of selected literary critical polemics from the 1930s and 1940s) - Martin Makara (Slovenska Literatura)
The article explores the relationship between the literary-critical aspiration for axiologically objective assessments of literary works and the variability of literary-critical evaluations in review practices. Based on research into literary criticism during the period between the two world wars, four variable factors in literary critical evaluation were identified as systematic components of evaluative literary reflection. These factors contribute to the inevitable evaluative differentiation within pluralistic critical practices. Within the fluctuating ontological framework of evaluation, the dispositive of the evaluating subject plays a significant role, since she co-creates the epistemological basis of evaluation (determining the text – understanding and interpreting it). This basis establishes the framework for selecting and applying axiological criteria – i.e., the relevant functions of a literary work and their corresponding norms. The influence of individual variable factors on the final evaluation of a literary work is demonstrated through period evaluative reflections on Slovak literary works from the 1930s and 1940s. These include Hmly na úsvite (Mists at dawn, 1930) by Milo Urban, Kus cukru (A lump of sugar, 1934) by Peter Jilemnický, Cesta zarúbaná (Blocked road, 1934) by Fraňo Kráľ, Kamarát Jašek (My friend Jašek, 1937) by Dobroslav Chrobák, and the poetry of Slovak Nadrealism.